Persepsi Mahasiswa Tentang Kreativitas Dosen Dalam Proses Belajar Mengajar Dan Minat Belajar Mahasiswa Terhadap Motivasi Belajar Mata Kuliah Akuntansi Perusahaan Jasa Pada Mahasiswa Pendidikan Akuntansi Di Universitas Muhammadiyah Surakarta Angkatan 2016/2017 - Budiantoro, Hery; , Drs. Sudarto, M.M (2017)
The purpose of this study is to determine whether there is an influence between the perceptions of students about the creativity of lecturers in the learning process and interest in learning motivation to study accounting courses services company on Accounting Education students Muhammadiyah University of Surakarta. The research used is quantitative associative method. The population in this study were 335 students and the sample taken 172 students taken by proportional technique non random sampling. Data collection techniques using questionnaires that have been tested with validity and reliability test. And continued by hypothesis test (normality test, linearity test, multicollinearity test, multiple regression, t test, f test, effective contribution and relative donation). The result of multiple regression analysis obtained: Y = 67,078 - 0,006 X1 + 0,557 X2 The equation shows that learning motivation is not influenced by student perception about lecturer creativity in learning process and influenced by interest in learning. The conclusion is: 1) there is no influence between the creativity of lecturers in teaching and learning process towards the motivation of studying accounting courses service company in Accounting Education students at Muhammadiyah University of Surakarta period 2016/2017, based on t test obtained tcount -0.092 <ttabel 1.974, and significant value 0.05. 2) there is a significant influence between the interest of learning on the motivation of studying accounting courses service companies in Accounting Education students at the University of Muhammadiyah Surakarta period 2016/2017, based on t test obtained t count 10,145> ttable 1,974, and significant value 0.05. 3) there is a significant influence between the creativity of lecturers in teaching and learning process and the interest of learning on the motivation of studying accounting courses service company at FKIP Accounting students at Muhammadiyah University of Surakarta period 2016/2017, based on F test obtained fcount> 76,354> ftabel 3,049, with significant 5%. The result of calculation for the value of R2 is obtained 47,5% meaning that student's motivation of FKIP Accounting is influenced by student perception about lecturer creativity in learning process and learning interest, and the rest 52,5% influenced by other variable not examined in this research.